From highlands to lowlands : Kelabit women and their migrant daughters - Poline, Bala (ISEAS–Yusof Ishak Institute, 2015)
This article examines the nature of agrarian transition and rural transformation in the Malaysian state of Sarawak on the island of Borneo. Although rural change is not new on the island, the speed and penetration wrought by current processes of change is far-reaching. The consequences have been uneven for indigenous communities: some have benefited from infrastructure projects like roads and schools and from proximity to employment in urban centers, but others have lost their land and face a depleted natural resource base and increasing difficulties in making a living in the village. This article argues that these processes are gendered in nature as men and women decide either to leave (whether singly or with their families) or stay put in the villages. Little research has been done on the gender dimension of agrarian transition in Sarawak. This article pieces together fragmented accounts to present a picture of how women effect as well as are affected by these changes.